Cortisol regulates the paracrine action of macrophages by inducing vasoactive gene expression in endometrial cells. Issue 6 (23rd December 2015) - Thiruchelvam, Uma; Maybin, Jacqueline A; Armstrong, Gregory M; Greaves, Erin; Saunders, Philippa T K; Critchley, Hilary O D
Abstract : Cortisol regulation of macrophages induces angiogenic gene expression in endometrial cells at menstruation. Abstract: The human endometrium undergoes inflammation and tissue repair during menstruation. We hypothesized that the local availability of bioactive glucocorticoids plays an important role in immune cell–vascular cell interactions in endometrium during tissue repair at menstruation, acting either directly or indirectly via tissue resident macrophages. We sought to determine whether endometrial macrophages are direct targets for glucocorticoids; whether cortisol-treated macrophages have a paracrine effect on angiogenic gene expression by endometrial endothelial cells; and whether endometrial macrophages express angiogenic factors. Human endometrium ( n = 41) was collected with ethical approval and subject consent. Donor peripheral blood monocyte-derived macrophages were treated with estradiol, progesterone, or cortisol. The effect of peripheral blood monocyte-derived macrophage secretory products on the expression of angiogenic RNAs by endothelial cells was examined. Immunofluorescence was used to examine localization in macrophages and other endometrial cell types across the menstrual cycle. Endometrial macrophages express the glucocorticoid receptor. In vitro culture with supernatants from cortisol-treated peripheral blood monocyte-derived macrophages resulted in altered endometrial endothelial cell expression of the angiogenic genes, CXCL2, CXCL8, CTGF, and VEGFC . These data highlight the importance of local cortisol in regulating paracrine actions of macrophages in the endometrium. CXCL2 and CXCL8 were detected in endometrial macrophages in situ. The expression of these factors was highest in the endometrium during the menstrual phase, consistent with these factors having a role in endometrial repair. Our data have indicated that activation of macrophages with glucocorticoids might have paracrine effects by increasing angiogenic factor expression by endometrial endothelial cells. This might reflect possible roles for macrophages in endometrial repair of the vascular bed after menstruation.